INFLUENCE OF MEAT TYPE ON PROCESSED MEAT (KILISHI) QUALITY (FUDMA JOURNAL OF SCIENCES, 2022)
Meat is a good source of quality protein but undergoes rapid deterioration due to physical, chemical and microbial influence. Hence, the need to develop a nutrient-dense product like kilishi with significant storage stability, increased cost efficiency, increased variety and promote food security. Kilishi was produced from different meat sources; beef (KB), chicken (KC), chevon (KV) and mutton (KM) and was assessed for proximate, physicochemical, mineral compositions, microbial quality and sensory properties using standard methods. The result showed proximate composition to range from 8.97 to 11.34%, 3.94 to 6.31%, 16.21 to 27.31%, 21.38 to 23.12% and 37.43 to 45.90% for moisture, ash, fat, protein and carbohydrate contents. Physicochemical properties ranged from  0.08 to 0.18 meg O2/kg for peroxide value, 0.06 - 0.41 TBARS/g for thiobarbituric acid value, 6.91 to7.54 for colour, 6.65 to 7.30 for pH and 61.25 to 69.40 mg/ml for solubility. Mineral composition showed that mutton meat kilishi (KM) had higher calcium (51.14 mg/100 g), magnesium (40.04 mg/100 g) and sodium (132.75 mg/100 g) contents while beef kilishi (KB) had the highest iron (8.24 mg/100 g) contents. Microbiologically, the kilishi samples were fit and safe for consumption. The organoleptic study revealed consumersâ€™ preference for beef samples. Kilishi production improved the nutrient density, stability and safety of meat from their respective meat sources, and will serve as a viable means of meat storage in low-income countries.
Keywords: Kilishi, Meat, Quality, Beef, Chicken, Chevon, Mutton